What Painting Is - Elkins, James (New York : Routledge, 1999)
In this classic text, James Elkins communicates the experience of painting beyond the traditional vocabulary of art history. Alchemy provides a strange language to explore what it is a painter really does in the studio—the smells, the mess, the struggle to control the uncontrollable, the special knowledge only painters hold of how colors will mix, and how they will look. Written from the perspective of a painter-turned-art historian, this anniversary edition includes a new introduction and preface by Elkins in which he further reflects on the experience of painting and its role in the study of art today. (provided by publisher)
boek